POOR AIR QUALITY POSES THREAT TO AIRLINE PASSENGERS, SMOKING BAN EFFECTIVE (Tufts Archival Research Center, 2007)
ACVA-Atlantic news release entitled “Poor Airline Cabin Quality Poses Threat to Passengers, Smoking Ban Ineffective.” Reports on Gray Robertson testimony at a Congressional Hearing claiming that indoor air pollution is increasing in aircraft as airlines attempt to cut costs and maintains that a smoking ban does not go far enough in addressing the problem. Suggests that improved ventilation and filtration systems would be more effective than a complete smoking ban.